The real exchange rate, fiscal deficits and capital flows India: 1981-2000 - Lal, Deepak; Pant, Devendra Kumar; Bery, Suman (2003)
India should use the opportunity presented by high reserves and low domestic inflation to now fully open the capital account (with a proviso about borrowing in foreign currency), make the rupee fully convertible and allow it to float freely. For in a world of fluctuating capital flows it is impossible for the authorities to predict, let alone implement, the requisite movements in the nominal exchange rate required for a managed float. If this is done, none of the fears that the authorities seem to have about absorbing capital inflows would be realistic and India could very quickly raise its growth rate, which continues to be suppressed by the misalignment of the real exchange rate. - Reproduced.
Keywords: Deficit financing - India; Capital flow - India; Exchange rates - India; Exchange rates